Demystifying the estimand framework: a case study using patient-reported outcomes in oncology. Issue 10 (October 2020) - Fiero, Mallorie H; Pe, Madeline; Weinstock, Chana; King-Kallimanis, Bellinda L; Komo, Scott; Klepin, Heidi D; Gray, Stacy W; Bottomley, Andrew; Kluetz, Paul G; Sridhara, Rajeshwari
Summary: Patient-reported outcome (PRO) measures describe how a patient feels or functions and are increasingly being used in benefit–risk assessments in the development of cancer drugs. However, PRO research objectives are often ill-defined in clinical cancer trials, which can lead to misleading conclusions about patient experiences. The estimand framework is a structured approach to aligning a clinical trial objective with the study design, including endpoints and analysis. The estimand framework uses a multidisciplinary approach and can improve design, analysis, and interpretation of PRO results. On the basis of the International Council for Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use E9(R1) addendum, we provide an overview of the estimand framework intended for a multistakeholder audience. We apply the estimand framework to a hypothetical trial for breast cancer, using physical function to develop specific PRO research objectives. This Policy Review is not an endorsement of a specific study design or outcome; rather, it is meant to show the application of principles of the estimand framework to research study design and add to ongoing discussion. Use of the estimand framework to review medical products and label PROs in oncology can improve communication between stakeholders and ultimately provide a clearer interpretation of patient experience in the development of oncological drugs.